Awareness in rolling, research about its effects and use of polyurethane memory foam - Paolo Gili (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Even though the rolling of paintings on canvas is a centuries-old tradition, it has not yet found scientific references for the identification of the best curve radius for the cylinder and for the most suitable packaging materials. Moreover, physical hazards connected with this risky procedure are often underestimated. The attempt to define guidelines for rolling up paintings led to the creation of a “flexometric table". Furthermore, an initial attempt to experiment with the use of two types of polyurethane foams led to the establishment of several tests which demonstrated its excellent characteristics during the rolling phase of the artworks, especially for textured ones.